Further notes on the genus Stenaelurillus Simon, 1885 from India (Araneae: Salticidae) - Logunov, Dmitri V. (Zootaxa, 2020)
Three new Indian species of Stenaelurillus Simon, 1885 are diagnosed, illustrated and described: S. indicus sp. nov. (♂♀, from Andhra Pradesh), S. tettu sp. nov. (♂♀, from Andhra Pradesh), and S. wandae sp. nov. (♂♀, from Odisha). A lectotype (♂) for S. lesserti Reimoser, 1934 from India is designated. A new record of S. lesserti from Andhra Pradesh and comments about its presence in Sri Lanka are provided. The localities of all the described and recorded species is mapped.